The impact of environmental information disclosure on enterprises’ green preference of outbound investment: Evidence from China - Peng, Cheng; Fu, Wenting; Jiang, Hui; Zou, Yu (Frontiers in Psychology, 2022)
Currently, China is in a period of accelerating green and low-carbon transformation and promoting high-quality economic development. In order to effectively contribute to the improvement of global environmental quality and enhance enterprises' awareness of environmental responsibility in the process of outbound investment, China strongly advocates that enterprises should comply with the environmental protection laws and regulations of host countries and try to strengthen local environmental protection as investing abroad. However, the influence factors of enterprises' green preferences in outbound investment has not yet received sufficient attention of scholars. Therefore, using a sample of Chinese A-share listed companies from 2008-2019, this paper aims to empirically analyse whether the quality of environmental information disclosure (QEID) would affect enterprises' green preference of outbound investment (OIGP), and the influence mechanism of QEID on the enterprises' OIGP by analyzing the mediating effects of green technology innovation and media attention. It found that, on the whole, the quality of environmental information disclosure will significantly promote the enterprises' OIGP. In terms of influence mechanism, QEID would promote firms' OIGP by restraining media attention, while the mediating role of green technology innovation in the effect of QEID on firms' OIGP is shown as the masking effect.